Bangladesh Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria-Staff Report; Debt Sustainability Analysis Update; and Press Release (IMF Staff Country Reports, 2014)
KEY ISSUES Context: Economic activity was disrupted by political unrest and uncertainty in the run-up to the January 2014 general elections. However, macroeconomic stability was maintained and international reserve buffers have been built up further. As calm returns following the elections and activity normalizes, growth is expected to recover in the second half of fiscal year 2014 (FY14, July 2013-June 2014) and in FY15, supported by domestic demand. Exports, on the other hand, face headwinds as the garment industry adjusts to higher costs from increased minimum wages and stricter labor and safety standards. A resurgence of political violence poses the main risk to the outlook. Program: The program, supported by a three-year Extended Credit Facility (ECF) arrangement for SDR 639.96 million (120 percent of quota) approved in April 2012, remains on track.